OP0069 Significantly Better Results for TNFI Combination Therapy with MTX Than TNFI Mono- and Combination Without MTX Therapy in Patients with RA: Results from the Dream Registry. (23rd January 2014) - Manders, S.; Kievit, W.; Jansen, T.; Stolk, J.; Visser, H.; Bos, R.; van de Laar, M.; van Riel, P.
Abstract : Background: Although it is advised to treat Rheumatoid Arthritis (RA) patients with Methotrexate (MTX) as co-medication in the treatment with Tumor Necrosis Factor inhibitors (TNFi), there is a body of patients that is treated with TNFi mono-therapy or combination therapy without MTX in daily clinical practice. We hypothesize a difference in effectiveness and drug survival between TNFi mono-therapy, combination therapy (TNFi + MTX) and non MTX-DMARD combination therapy. Objectives: To compare TNFi mono-therapy with TNFi combination therapy with and without MTX on drug survival and DAS28 over time in patients with RA. Methods: Data from the DREAM registry was used. Patients starting with their first TNFi treatment were analyzed, comparing mono-therapy and combination therapy with and without MTX. Drug survival was analyzed with Kaplan-Meijer and Cox regression. Effectiveness on DAS28 was analyzed by repeated measure analyses. Both analyses were corrected for confounders (age, gender, disease duration, weight, erosive disease, rheumatoid factor, DAS28 + HAQ-DI at baseline). Results: 261 patients started mono-therapy, 335 combination therapy without MTX, and 1337 with MTX. The 3 groups differed at some baseline characteristics: % female (74.3, 71.9, 66.9), disease duration (10.3, 10.3, 9.2), and DAS28 (5.15, 4.98, 4.87) and HAQ-DI at baseline (1.44, 1.45, 1.30) (p-value < 0.1). Combination therapy with MTX had a significantly longer drug survival (Figure1), median time of use 6.0, 1.3 and 2.6 years respectively, (p-value=0.000), and significantly better DAS28 (Figure2) over time (p-value=0.000), both after correction for confounders, than the mono- and the combination without MTX therapy group. Combination therapy without MTX had a significantly longer drug survival than mono-therapy (p-value=0.000) but no better DAS28 over time (p-value=0.245). Image/graph: Conclusions: All 3 therapy strategies provide positive outcomes but combination therapy with MTX is significantly better than TNFi mono-therapy and combination therapy without MTX in daily practice. Therefore it is important that rheumatologists follow the recommendations of the clinical guidelines and prescribe TNFi with MTX as co-medication. If this is not possible, combination therapy without MTX is the next best alternative for better drug survival. Disclosure of Interest: None Declared